Poor attainment of blood pressure, lipids and diabetes targets in people at high cardiovascular risk in Europe: a report from the ESC-EORP EUROASPIRE V Survey in 16 European countries. (25th November 2020) - Kotseva, K; De Backer, G; De Bacquer, D; Grobbee, D; Hoes, A; Jennings, C; Maggioni, A; Marques-Vidal, P; Ryden, L; Wood, D
Abstract: Introduction: The EUROASPIRE V survey in primary care was carried out by the European Society of Cardiology, EURObservational Research Programme in 2017–2018 and investigated the risk factor management in patients at high cardiovascular (CVD) risk in16 European countries. Purpose: To provide an audit the implementation of the 2016 Joint European Societies' guidelines on CVD prevention in people at high risk of developing CVD in primary care and to see whether the practice of preventive cardiology had improved by comparison with the previous EUROASPIRE IV survey in 2014–2015. Methods: All patients were free of coronary or other atherosclerotic diseasebut considered at high CVD risk since they had been started on blood pressure and/or lipid and/or glucose lowering treatments. They were interviewed and examined by means of standardized methods ≥6 months after the start of therapy. Results: 2, 759high CVD risk individuals (58% females), mean age 59 (SD 12) years, were interviewed and examined (participation rate 70%). The risk factor control was very poor, with less than half (47%) of patients on blood pressurelowering medication reaching the target of <140/90 mmHg (<140/85 mmHg in people with self-reported diabetes). Among treated dyslipidaemic patients only 47% attained LDL-cholesterol target of <2.6 mmol/L. Among treated type 2 diabetic patients, 65% achieved the HbA1c target of <7.0mmol/L. However, many patients on no antihypertensive or lipid-lowering medications had elevated blood pressure (43%) and elevated LDL-cholesterol (81%), respectively. The use of blood pressure lowering medication in people with hypertension was: ACE inhibitors/ARBs 79%, beta-blockers 37%, diuretics 36% and calcium channel blockers 32%; with 42% on one, 34% on two, 18% on three and 6% on ≥4 blood pressure lowering drugs. Among people on lipid-lowering medication, statins were prescribed in 97% and fibrates in 3%. Less than two-thirds of patients reported complete adherence with the intake of their blood pressure and lipid-lowering medications. The comparison with EUROASPIRE IV in the same centres that took part in both surveys showed no change in the BP management. There was a slight improvement in the control of LDL-cholesterol and glucose in patients with diabetes. Conclusions: The results of EUROASPIRE V clearly demonstrate that the control of blood pressure, LDL-cholesterol and diabetes in patients at high CVD risk remains poor with large proportions not achieving the targets defined in the prevention guidelines. There is a considerable potential to raise the standards of preventive cardiology and to improve the management of patients at high CVD risk in Europe. Funding Acknowledgement: Type of funding source: Other. Main funding source(s): European Society of Cardiology